If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 8lnx = 26 Solving 2 + 8lnx = 26 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 8lnx = 26 + -2 Combine like terms: 2 + -2 = 0 0 + 8lnx = 26 + -2 8lnx = 26 + -2 Combine like terms: 26 + -2 = 24 8lnx = 24 Divide each side by '8nx'. l = 3n-1x-1 Simplifying l = 3n-1x-1
| 24.4-4p=53.3 | | 15+3x+6=-7x+2x+2 | | 12r^2+21r-8r-14=0 | | 2x+2=-5x+23 | | 6x+11=2x+47 | | 16a+3= | | y-5=0x-7 | | p(x)=[x-(1+2i)][x-(1-2i)](x-2)(x+1) | | 3xy+7x+6x+8xy= | | p=-12.5t+100 | | 0.5y+0.2y=0.3y+2 | | 13-1(2x+4)=35 | | 3.1x+2=-0.5 | | 15+-8=x | | 4(2x-3)(4x+5)=0 | | 6(a+2)-2(2a+5)=18 | | 12x^2+24x-288=0 | | (7x+16)+(9x-12)=180 | | 15x+3x=180 | | 9t+-21=3(t+-7)+6t | | 4(3x+1)+4=13x+4 | | 15x-9-4x+9= | | n^2+n=45 | | 9l-22=23+4l | | X=-8+15 | | 4m+6=17 | | 13w+39= | | y-2=.666x-27 | | 3.3x-4.2=-0.4 | | y-(-5)=-11 | | 11y-7.5-7y=2 | | C=3.50p+550 |